Development and validation of the Spanish Work-Family Conflict Scale (SP-WFCS): evidence from two independent samples in Argentina - Pujol-Cols, Lucas J. (2021)
Research on work-family conflict has increased dramatically in recent years. In this study, we developed a Spanish version of the Work-Family Conflict Scale (Carlson et al. Journal of Vocational Behavior, 56(2), 249-276, 2000) and examined its reliability, dimensionality, factor invariance, gender invariance, convergent validity, discriminant validity, and empirical validity. To this end, we analyzed data collected from two independent samples of Argentinian employees (N = 618). The results from the confirmatory factor analysis (CFA) revealed that the Spanish Work-Family Conflict Scale (SP-WFCS) displayed a six-dimensional factor structure (CFI ≥ .96, TLI = .96, RMSEA = .06). Furthermore, each dimension showed satisfactory levels of internal consistency (α estimates ranged from .80 to .92), convergent validity (AVE estimates ranged from .59 to .80, and CR estimates ranged from .81 to .92) and discriminant validity (AVE values ≥ shared variance estimates). Moreover, the results from the multi-group confirmatory factor analyses indicated that the six-dimensional model of the SP-WFCS was statistically invariant across samples and gender. Finally, most work-family conflict dimensions displayed significant correlations with three antecedents (i.e., quantitative demands, emotional demands, and core self-evaluations) and two outcomes (i.e., affective job satisfaction and burnout). Taken together, the results provided support to the validity of the SP-WFCS in Argentina, suggesting that it may be a reliable and valid instrument to measure work-family conflict in Spanish-speaking countries. Limitations to the study and opportunities for future research are discussed in this article.